Implementasi dan Manfaat Ice Breaking pada Proses Pembelajaran di Tingkat SMP - Putri Adilah Prautami; Hindun Hindun (LPPM Politeknik Pratama, 2023)
This research aims to examine the implementation and benefits of ice breaking in the learning process at the junior high school level through the literature study method. By analyzing relevant literature, this research presents a comprehensive picture of how ice breaking has been applied in the context of learning in junior high school. The ice breaking method is adopted as an opening strategy to overcome initial awkwardness and build positive interactions among learners. The results show that the consistent implementation of ice breaking provides significant benefits for both learners and educators. For learners, this activity increases engagement, confidence and motivation to learn. In addition, ice breaking helps build social skills and teamwork. For educators, ice breaking becomes an effective tool to open communication channels with students, understand individual needs and create an inclusive learning environment. This research provides insights into the successful implementation and benefits that can be derived from the application of ice breaking in the context of junior secondary education.